2017
DOI: 10.1007/s12678-017-0367-9
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Photosynthesis System Based on Ti/TiO2 Coated with Cu(II) Aspirinate Complex for CO2 Reduction to Methanol

Abstract: A novel copper(II) aspirinate complex easily deposited onto nanotubes of Ti/TiO 2 was successfully employed in the conversion of CO 2 to methanol through the use of UV-Vis irradiation coupled to a bias potential of −0.35 V vs saturated calomel electrode. An average concentration of 0.8 mmol L −1 of methanol was obtained in 0.1 mol L −1 of sodium sulfate saturated with CO 2 using a self-organized Ti/ TiO 2 nanotubular array electrode coated with a [Cu 2 (asp) 4 ] complex. The influence exerted by CO 2 and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
1
7
0
2
Order By: Relevance
“…In the presence of CO 2 in the same experimental conditions, the I ph vs. E curves showed a decreasing of the photocurrent in the cathodic region of 208% and 187% for Ti/TiO 2 NT (Curve 4) and Ti/TiO 2 NT-ZrO 2 (Curve 5), respectively. This behavior suggested that the CO 2 in solution can be acting as a scavenger of photogenerated electrons [24,45], consequently reducing the photocurrent.…”
Section: Photoactivity Of Ti/tio 2 Nt-zro 2 Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of CO 2 in the same experimental conditions, the I ph vs. E curves showed a decreasing of the photocurrent in the cathodic region of 208% and 187% for Ti/TiO 2 NT (Curve 4) and Ti/TiO 2 NT-ZrO 2 (Curve 5), respectively. This behavior suggested that the CO 2 in solution can be acting as a scavenger of photogenerated electrons [24,45], consequently reducing the photocurrent.…”
Section: Photoactivity Of Ti/tio 2 Nt-zro 2 Electrodesmentioning
confidence: 99%
“…The use of p-n type semiconductor heterojunctions has been explored as a way to enhance the photoelectrocatalytic performance of photoelectrodes [10,[22][23][24][25][26]. The heterojunction can improve the separation of electron/hole pairs, since the charge transfer can be amplified.…”
Section: Introductionmentioning
confidence: 99%
“…The electrons driven to the photocatalyst surface in a photoelectrocatalytic process [33] play a major role in the conversion of CO 2 to fuels or other chemical products. This is an attractive process, although remaining challenges include low dissolution of CO 2 in aqueous media and poor selectivity of the CO 2 reduction reaction [24,25,[29][30][31][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The photoelectrocatalytic conversion of dissolved CO 2 in aqueous solution is complex. A high efficiency can be obtained for catalyst with high ability to chemisorb and activate the CO 2 and it depends of (i) the semiconductor type used as photocathode [ [3], 12,13], (ii) the irregularities of the surface that can display different CO 2 adsorption modes [14], (iii) the supporting electrolyte [3], (iii) the pH of the solution [12], (iv) the applied potential [13], (v) the photoelectrocatalysis time [15], the photoelectrocatalytic reactor design [ [3], 15,17,18] and others.…”
Section: Introductionmentioning
confidence: 99%
“…The steps are based on the transfer of multiple photogenerated electrons (conversion to methanol requires six electrons) and also the formation of hydrogen radical relevant to produce hydrocarbon from carbon dioxide [28]. The literature has reported that p-n junction semiconductors can be a good alternative to enhance the photoelectrocatalytic performance [15,13,[29][30][31][32]. The heterojunction can enhance the separation of electron-hole pairs, since the charge transfer can be amplified by the Z-scheme mechanism [17,32], facilitating these multiple steps.…”
Section: Introductionmentioning
confidence: 99%